Correlative factors of ocular surface lesions after allogeneic hematopoietic stem cell transplantation: A retrospective study - Zhuang, Xin-Yu; Sun, Zheng-Tai; Xu, Yue; Ren, Ya-Ru; Chen, Ying-Jie; Chen, Feng; Ma, Xiao; Tang, Xiao-Wen; Zhang, Xiao-Feng (Frontiers in Oncology, 2022)
Background Ocular graft-versus-host disease (oGVHD) is one of the complications after allogeneic hematopoietic stem cell transplantation (HSCT), which impairs the quality of life and may indicate poor prognosis. In this retrospective study, the aim was to investigate the characteristics of ocular surface after HSCT, and analyze the risk factors related to the severity of ocular surface lesions. Methods 248 post-HSCT patients were enrolled in this retrospective study. Subjects were divided into no lesion group, mild lesion group and severe lesion group, according to the severity of ocular surface lesions. The correlations between grades of ocular surface lesions and gender, age, primary disease, donor source, human leukocyte antigen (HLA) type, kinship, donor-recipient relationship, blood type, source of stem cell and systemic GVHD were analyzed. Results The median scores of corneal epitheliopathy, lid margin lesions and meibomian gland loss were 3, 6 and 2 points, respectively. The grade of corneal epitheliopathy was related to donor source (P<0.001), kinship (P=0.033), HLA-matching (P<0.001), and systemic GVHD (P=0.007), especially oral GVHD (P<0.001) and liver GVHD (P=0.002). The grade of lid margin lesions was related to donor source (P=0.019), HLA-matching (P=0.006), and systemic GVHD (P=0.013), especially skin GVHD (P=0.019) and oral GVHD (P=0.019). The grade of meibomian gland loss was related to age (P=0.035) and gastrointestinal GVHD (P=0.007). The grade of corneal epitheliopathy after HSCT was related to the lid margin lesion score (P<0.001). Conclusions The occurrence and development of ocular GVHD are mostly accompanied by the history of systemic GVHD. While in few cases, ocular surface lesions related to GVHD can be observed prior to the rejection of other tissues and organs. Severe corneal epitheliopathy occurs in patients with severe lid margin lesions in ocular GVHD. The lesions of corneal epithelium and lid margin are milder in HLA partially matching transplantation.